The Social Psychology of Inequality 2019
DOI: 10.1007/978-3-030-28856-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Social Class Differences in Social Integration at University: Implications for Academic Outcomes and Mental Health

Abstract: University represents a pathway to upward social mobility for many working-class people. However, this distinctly middle-class environment also provides a number of unique social psychological challenges for working-class students. Working-class university students are often in the minority group at university, they are often the first in their families to attend university, and they often feel out of place at university. They also lack the time and money required to engage with other students on campus. Conse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…Students from lower socioeconomic (SES) backgrounds tend to have poorer mental health at university than students from higher SES backgrounds (Ibrahim et al, 2013 ; King et al 2011 ; Rubin et al 2016 ; Rubin and Kelly 2015 ; Said et al 2013 ; for a recent review, see Rubin et al 2019 ). Prior work in this area has found that classism, sense of control, social contact with other students, and parenting style operate as mediators (Allan et al 2016 ; Ibrahim et al 2013 ; Rubin et al 2016 ; Rubin and Kelly 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Students from lower socioeconomic (SES) backgrounds tend to have poorer mental health at university than students from higher SES backgrounds (Ibrahim et al, 2013 ; King et al 2011 ; Rubin et al 2016 ; Rubin and Kelly 2015 ; Said et al 2013 ; for a recent review, see Rubin et al 2019 ). Prior work in this area has found that classism, sense of control, social contact with other students, and parenting style operate as mediators (Allan et al 2016 ; Ibrahim et al 2013 ; Rubin et al 2016 ; Rubin and Kelly 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several steps that institutions of higher education can take to improve belonging socialization effectiveness. Colleges and universities may seek to promote interdependent values on college campuses, which first-generation students and students of color tend to endorse (Rubin et al, 2019; Stephens et al, 2017). Such strategies have been successful in increasing underrepresented students’ motivations and intentions to persist in college, including underrepresented group members’ interest in STEM (Boucher et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Further, student socialization activities, such as student orientations, tend to address the needs of White, middle-class students more than those of students of color and first-generation students (Rubin et al, 2019; Stephens et al, 2017). Colleges often encourage and celebrate individual accomplishments and thought, for example, finishing an honors thesis or encouraging students to challenge ideas and find their own voice.…”
Section: New Student Socializationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a growing number of studies have shown sense of belonging to be positively associated with mental health, which in turn contributed to academic success (Azmitia et al, 2013;van der Zanden et al, 2018). Nevertheless, studies focusing on student mental health as an outcome, while assessing the importance of sense of belonging, are limited (Dixon & Kurpius, 2008;Rubin et al, 2019;Stebleton et al, 2014;Wörfel et al, 2015).…”
mentioning
confidence: 99%